Protein Kinase Induction in Escherichia coli by Bacteriophage T7 - Rahmsdorf, H. J. (1974)
After bacteriophage T7 infection, a protein kinase (EC 2.7.1.37; ATP:protein phosphotransferase) activity can be demonstrated in E. coli in vivo by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and autoradiography. Cell-free extracts catalyzed the transfer of the terminal phosphoryl group of [(γ)-(32)P]ATP to endogenous protein acceptor or to added histone. The bond between phosphate and protein shows the characteristics of serine phosphate: it is stable in 1 N HCl (100°) and cleaved by 1 N KOH (37°) and by alkaline phosphatase treatment. Moreover, after partial acid hydrolysis, radiophosphate migrates with marker O-phosphoserine on polyethyleneimine-cellulose thin-layer chromatograms. Enzyme activity in uninfected cells is negligible. Ultraviolet irradiation of the phage genome prevents the appearance of the protein kinase; irradiation of the host genome does not. The enzyme activity occurs 4 min after infection and its gene maps in the early region (promoter proximal to gene 1). Ribosomal proteins are phosphorylated in vivo and are substrates in vitro. Enzyme activity in vitro is not changed by addition of cyclic AMP or cyclic GMP.